HUBUNGAN LAMA PEMAKAIAN DEPO MEDROXY PROGESTERON ASETAT DENGAN KENAIKAN BERAT BADAN DIPUSKESMAS KASSI-KASSI MAKASSAR - asmah asmah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2020)
Objective: To know the relation between the depo medroxy progesterone acetate and weight gain in puskesmas kassi-kassi makassar. Method: This research use analytical survey method with cross sectional study approach. The total population in the study were 407 respondents and 100 respondents samples. Sampling with purposive sampling technique. Research instrument in the form of check list sheets in the analysis using statistical test Chi square. Results: The results showed that from 100 respondents studied, respondents who experienced weight gain were 67 respondents (67.0%) and those who did not change the weight of 33 respondents (33.0%). The results showed that ? = 0,557> ? = 0,05 which means Ho not accepted and stated that there is no relationship of weight change with side effect of 3 month injection. Discussion: Factors that affect weight change in injecting contraceptive contraceptives are the presence of a strong progesterone hormone that stimulates the appetite hormone present in the hypothalamus. Appetite is more than usual because the body of excess nutrients that by the hormone progesterone changed to fat and stored under the skin. This weight change is due to excessive accumulation of fat from the synthesis of carbohydrates to fat, progesterone increases basal insulin levels and insulin induced by digested carbohydrates. Conclusion: Conclusions and suggestions no long-term use association with weight gain on the use of medroxy progesterone acetate depo injection. It is expected that midwives or implementers of family planning programs always provide information about family planning for prospective acceptors either in the form of counseling services or health promotion media